TERAPI TROMBOLISIS INTRAVENA PADA PASIEN STROKE ISKEMIK DENGAN AWITAN KURANG DARI 6 JAM - Muhammad Kurniawan, Ramdinal Aviesena Zairinal, Taufik Mesiano, Rakhmad Hidayat, Salim Harris, Teguh (Neurona Majalah Kedokteran Neuro Sains, 2014)
CASES OF ACUTE STROKE WITH 4 HOURS ONSETWERE INCLUDED INTO THE CIPTO MANGUNKUSUMO HOSPITAL RSCM CODE STROKE PROTOCOLS AT THE EMERGENCY ROOM OF THE RSCM JAKARTA CLINICAL EXAMINATION AND NEUROIMAGING WERE PERFORMED IMMEDIATELY THE TIME NEEDED FOR THE INTERPRETATION OF COMPUTED TOMOGRAPHY SCAN CT SCAN WAS 30 MINUTES FROM PATIENTS ARRIVAL TO CONFIRM ABSENCE OF INTRACRANIAL BLEEDING INTRAVENOUS THROMBOLYSIS THERAPY USING ALTEPLASE 06MGKG BODY WEIGHT WAS THEN GIVEN STRICT 24HOUR MONITORING WAS CARRIED OUT TO CONTROL BLOOD PRESSURE AND OTHER METABOLIC PARAMETERS DURING THE TREATMENT PERIOD THE PATIENTS IMPROVED CLINICALLY THE PATIENTS NIHSS SCORES UPON ADMISSION AND DISCHARGE WERE 7 AND 4 RESPECTIVELY INTRACRANIAL BLEEDING COMPLICATIONS DID NOT OCCUR